Teleconsultations by doctors and nurses from Primary Care in Florianópolis during the Covid-19 pandemic: a retrospective study - Rebolho, Ricardo Collar; Lúcio, Donavan de Souza; Raupp, Fabiano Maury (Medicina (Ribeirao Preto), 2023)
Introduction: Teleconsultations were only allowed by class councils in Brazil after the start of the Covid-19 pandemic. The Primary Care (PC) of Florianópolis met the conditions to make teleconsultations and was the first capital to adopt this model of assistance on a large scale. Objective: Compare the conditions of care and the characteristics of health professionals in consultations held at the Florianópolis PC by doctors and nurses between teleconsultations and face-to-face consultations. Methodology: Retrospective study with all consultations carried out by doctors andnurses of the PC from 04/15/2020 to 07/27/2020. Results: We analyzed 225,507 consultations performed by 436 doctors and nurses. Professionals, doctors and nurses, who performed at least one teleconsultation had a higher number of consultations, a slightly longer average consultation time, as well as a slightly higher average number ofreferrals and tests requested per consultation. Teleconsultations were faster, had fewer tests requested, medications prescribed and referrals made. The conditions least evaluated by teleconsultation were: cervical cancer screening,impacted cerumen, tonsillitis and childcare. The conditions most evaluated by doctors and nurses in teleconsultations were: hypothyroidism, dyspepsia, contraception and unclassified pain. Conclusions: Teleconsultation is a useful tool for providing care in the PC and allows the care of a wide range of conditions. It is important to carry out studies of this technology in this period of exception to support future decisions when maintaining it after the pandemic.